Labelling Approaches for Supplemented Foods - Wahba, Rana (Université d'Ottawa / University of Ottawa, 2018)
In recent years, natural health products in food formats with higher levels of added vitamins and minerals, amino acids, herbal ingredients and bioactives sought and were granted market access in Canada. Since these food products, referred to as supplemented foods (SFs), are sold alongside conventional foods and lack features that clearly distinguish them from other foods, there is a potential for confusion among consumers as to the appropriate use of these products. There is no research evaluating the nutrition labelling approaches for these foods, and what consumers need in a labelling approach to be able to identify these food products and distinguish them from other foods, determine what the supplemental ingredients are and understand any directions or cautions for use of these foods. To determine key components of an appropriate labelling approach, interviews and discussion groups were conducted in the National Capital Region and the surrounding area to assess consumer access, understanding and appraisal of these foods, using current and tested labelling strategies. Consumer feedback consistently indicated that the current labelling is insufficient for awareness, understanding, appraisal and appropriate use of supplemented foods. Tested labelling components that facilitated awareness, understanding, and appraisal of supplemented foods included a symbol based supplemented food product identifier with the wording “Supplemented” on the front of the package, a “Supplemented” information box containing a listing of the name and amount of each supplemental ingredient and cautionary labelling in proximity to the supplemental ingredient labelling. These key labelling components are to be integrated into a web-based mock-package trial that will objectively test these labelling tools on a large sample of Canadian consumers (n=4000).
Keywords: Nutrition labelling; Supplemented Foods; Supplemental ingredients